Prediction of Pharmacokinetics and Pharmacodynamics of Doripenem in Pediatric Patients. Issue 9 (26th March 2015) - Matsuo, Yumiko; Ishibashi, Toru; Shimamura, Kenji; Wajima, Toshihiro; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> The aim of this paper was to predict the pharmacokinetics of doripenem in pediatrics from adult pharmacokinetic data and to investigate dosing regimens in pediatrics using Monte‐Carlo pharmacokinetics/pharmacodynamics (PK/PD) simulations prior to the initiation of pediatric clinical trials. The pharmacokinetics in pediatrics was predicted by using a previously reported approach for β‐lactam antibiotics. Monte‐Carlo simulation was employed to assess dosing regimens in pediatrics based on the predicted pharmacokinetic profiles and the minimum inhibitory concentration (MIC) distributions of Haemophilus influenzae and Streptococcus pneumoniae, which frequently cause infectious pediatric diseases. The probabilities of attaining target time above MIC (40%T>MIC) were calculated for dosing regimens of 1–30 mg/kg with two or three times daily dosing (TID) based on simulations of 5000 pediatric patients and MICs. The results suggested 15 and 5 mg/kg TID would give approximately 90% or more probability of target attainment against Haemophilus influenzae and Streptococcus pneumoniae, respectively. The pediatric phase 3 study confirmed that pharmacokinetics in pediatrics could be well predicted by this method, indicating that the dosing regimen had been appropriately selected. The framework of dose selection for pediatric clinical trials based on predictions of pharmacokinetic profiles and PK/PD indices should be applicable to the development of other β‐lactam antibiotics for pediatric use. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3194–3198, 2015